Hutchinson Gilford Progeria Syndrome (HGPS): Potential Treatments - Dias Rima Sutiono; Fransiska Adeline (PT Kalbe Farma Tbk., 2018)
The Hutchinson-Gilford Progeria syndrome (HGPS) is a rare genetic disease that causes an early accelerated aging in children; clinically characterized by manifestations affecting the skin, musculoskeletal system and blood vessels, also other features supporting aging processes. This disease affects 1 in 4 - 8 million newborns all over the world without any race and gender preferences. The clinical features of HGPS usually appear at the age of two and will be discovered through clinical diagnosis. It then will be followed by health problems like coronary atherosclerosis that can be life-threatening. The life-span is usually 14,6 years. This review will discuss some emerging potential treatment such as FTI (Farnesyltransferase inhibitors). Sindrom Hutchinson-Gilford Progeria adalah penyakit genetik langka berupa penuaan lebih cepat pada usia anak-anak ditandai beberapa manifestasi di antaranya kulit, sistem muskuloskeletal dan pembuluh darah, serta hal lain sesuai proses penuaan. Penyakit ini terjadi pada 1 di antara 4-8 juta bayi baru lahir di seluruh dunia tanpa preferensi ras dan gender. Gambaran klinis HGPS biasanya muncul di usia dua tahun, diikuti masalah kesehatan seperti aterosklerosis pembuluh darah koroner yang dapat mengancam jiwa. Rentang hidup pasien HGPS biasanya 14,6 tahun. Ulasan ini mengenai beberapa pengobatan potensial seperti FTI (inhibitor Farnesyltransferase).